Moderate deviations for sums of dependent claims in a size-dependent renewal risk model. Issue 7 (3rd April 2017) - Fu, Ke-Ang; Shen, Xinmei
ABSTRACT: In this article, we consider a non standard renewal risk model, in which pairs of claim sizes and its corresponding inter-arrival times are identically distributed, and each pair obeys a dependence structure. By assuming that the claim sizes form a sequence of extended negatively dependent random variables with consistently varying tails, moderate deviations for the aggregate amount of dependent claims are obtained.